Numerical computation of blood hemodynamic through constricted human left coronary artery: Pulsatile simulations. (December 2020) - Pandey, Rupali; Kumar, Manoj; Srivastav, Vivek Kumar
Highlights: The left coronary artery is constructed using CT images of healthy patients. Further, we have extended this geometry to 25%, 50%, and 75% blocked arterial geometries. Non-Newtonian Carreau viscosity model is enforced to interpret the blood hemodynamic at different levels of blockage over the entire cardiac cycle. Also, a comparison is made between the steady and pulsatile blood motion to interpret its effects on Coronary Artery Disease. It is concluded that the pulsatile flow in combination with distinct features of geometry such as branch junctions, curved sections, and flow constrictions can drive a blend of perplexing flows. The results will be useful for the Medical Practitioner to diagnosis, prognosis and treatment of the coronary artery diseases. Abstract: Background and objective: The accumulation of plaque in the coronary artery of the human heart restricts the path of blood flow in that region and leads to Coronary Artery Disease. This study's goal is to present the pulsatile blood flow conduct through four different levels of constrictions, i.e., healthy, 25%, 50%, and 75% in human left coronary arteries. Methods: Using CT scan data of a healthy person, the two-dimensional coronary model is constructed. A non-Newtonian Carreau model is used to study the maximum flow velocity, streamline effect, and maximum Wall Shear Stress at the respective constricted areas over the entire cardiac cycle. Finite Volume Method is executed for solving the governing equations. The fluctuating Wall Shear Stress (WSS) at different levels was assessed using Computational Fluid Dynamics (CFD). Results: The comparative study of the diseased arteries showcases that at the systolic phase, the 75% blocked artery attains the maximum velocity of 0.14 m/s and 0.53 m/s at t =0.005 s and t =0.115 s, respectively. While the maximum velocity takes a significant drop at t =0.23 s and t =0.345 s, this marks the diastolic phase. The streamline contour showcased the blood flow conduct at different phases of the cardiac cycle. At the peak systolic phase, a dense flow separation was observed near the blocked regions. It highlights the disturbed flow in that particular region. The most severely diseased artery acquires the maximum WSS of 18.81 Pa at the peak systolic phase, i.e., at t =0.115 s. Conclusions: The computational study of the hemodynamic parameters can aid in the early anticipation of the degree of the severity of the diseased arteries. This study, in a way, could benefit doctors/surgeons to plan an early treatment/surgery on the grounds of the severity of the disease. Thus, a before time prognosis could restrain the number of deaths caused due to Coronary Artery Disease.